2022
DOI: 10.3390/pathogens11091060
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Group B Streptococci in Lithuania Identifies Multi-Drug Resistant Clones and Sporadic ST1 Serotypes Ia and Ib

Abstract: Streptococcus agalactiae (Group B Streptococcus, GBS) is a leading cause of neonatal infections. Yet, detailed assessment of the genotypic and phenotypic factors associated with GBS carriage, mother-to-baby transmission, and GBS infection in neonates and adults is lacking. Understanding the distribution of GBS genotypes, including the predominance of different serotypes, antimicrobial resistance (AMR) genes, and virulence factors, is likely to help to prevent GBS diseases, as well as inform estimates of the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
(64 reference statements)
3
3
0
Order By: Relevance
“…Of these, CC1 (33.71%, n = 30/89) and CC19 (25.84%, n = 23/89) were the most prevalent, followed to a lesser extent by the hypervirulent CC17 (11.24%, n = 10/89). Overall, the population structure of GBS isolates in this study correlates with previously published data reporting the same dominant CCs among colonizing and infecting isolates ( Bianchi-Jassir et al., 2020 ; McGee et al., 2021 ; Rodgus et al., 2022 ). Nevertheless, the study showed that these main GBS lineages displayed varying levels of intra-lineage serotype diversity.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Of these, CC1 (33.71%, n = 30/89) and CC19 (25.84%, n = 23/89) were the most prevalent, followed to a lesser extent by the hypervirulent CC17 (11.24%, n = 10/89). Overall, the population structure of GBS isolates in this study correlates with previously published data reporting the same dominant CCs among colonizing and infecting isolates ( Bianchi-Jassir et al., 2020 ; McGee et al., 2021 ; Rodgus et al., 2022 ). Nevertheless, the study showed that these main GBS lineages displayed varying levels of intra-lineage serotype diversity.…”
Section: Discussionsupporting
confidence: 89%
“…Of particular concern was the high proportion of isolates with reduced susceptibility to macrolides and lincosamides, which are the antibiotics of choice for the treatment of GBS infections in patients with penicillin allergies. Here also, the molecular mechanisms of resistance to these antibiotics were consistent with those previously described for this species ( Bergal et al., 2015 ; Jin et al., 2022 ; Rodgus et al., 2022 ; Khan et al., 2023 ). Phylogenetic analysis showed that resistance to macrolides and lincosamides was not necessarily linked to the expansion of certain CCs but was distributed across all detected CCs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations